Glycoligands for targeted liposomes: design, development and ab-initio understanding of cell-vesicle recognition - Catania, Rosa (2018)
In nature, several known proteins are glycosylated, and carbohydrate-cell receptor interactions mediate a plethora of key biological events, e.g. parasitisation and immune responses. Cell membranes display carbohydrate-binding proteins (lectins), which are able to selectively recognise specific sugar-ligands, decipher sugar-encoded instructions, and convert them into downstream biological processes. To overcome low binding affinities, which are typically observed for simple monosaccharides, protein-binding sugars are typically displayed within large multivalent ligands, where biological systems rely on multivalent interactions as a way to enhance selectivity and binding avidity. Glycoliposomes, phospholipid vesicles coated with sugars, can be designed to exploit this phenomenon through the presentation of multiple glycosylated ligands for actively targeting specific receptors, enhancing uptake of nanomedicines into target cells, or both. Among all the nanocarriers, liposomes are an advantageous strategy for drug delivery for their biocompatibility and high drug encapsulation efficiency. Functionalised liposomes have been developed over the last 30 years to optimise these nanocarriers by improving stability, circulation time and targeting. This thesis work focussed on the use of glycosylated liposomal systems for the treatment of intracellular bacterial infection in cells presenting lectin endocytic receptors. Antimicrobial resistance is one of the current main global healthcare challenges. In particular, antimicrobial resistance in Salmonella Enterica serotypes is responsible for 16 million cases of typhoid fever, 94 million cases of gastroenteritis and 600.000 deaths worldwide. Salmonella is able to survive in intracellular compartments of macrophages. Mannose Receptor (MR, CD206) is a potential access gate to Salmonella infected macrophages which could be selectively targeted with mannosylate-decorated liposomes. In this work, we present the design, the development and investigation of liposomal systems to deliver antimicrobials into Salmonella-infected macrophages. In order to investigate and identify the key structural parameters for efficient delivery of glycotargeted liposomes to selected cell targets (MR+ macrophages), two sets of monovalent glycoligands and two sets of multivalent polyglycosides - synthetic lipid-terminated glycopolymers - bearing a range of membrane-inserting anchors were synthesised. These synthesised membrane-inserting glycoligands have been used to formulate glycosylated liposomes with different glycosylation patterns and lipid composition through the Bangham method. Concanavalin A – a carbohydrate-binding protein – has been initially utilised as model protein target to study the surface presentation of the carbohydrate ligands. Firstly, the effect of lipid composition on the rate of liposomal clustering mediated by Concanavalin A (Con A) model lectin has been established. Our results showed that the binding properties of glycoliposomes are affected by the nature of both lipid constituents and carbohydrate ligands. Next, the uptake of glycosylated liposomes was investigated in salmonella infected macrophage-like cells. This in vitro infection model was used to evaluate the effect of different glycosylation patterns on the liposomal surface on mannose receptor (MR, CD206) targeting efficacy. Liposomes coated with mannose-containing glycopolymer significantly enhanced uptake compared to uncoated liposome control, and showed higher gentamicin delivery, resulting in reduction in internal infection.